Methylated ARHGAP40 DNA as a potential biomarker for early diagnosis in high-grade ovarian serous cancer - Jiaxin Chai; Dongni Leng; Shuwei Guo; Rusong Zhang; Jiandong Wang; Yun Gu; Qiu Rao (Journal of Ovarian Research)
Abstract Ovarian cancer ranks as the eighth most common malignancy in women globally. Early detection remains a critical challenge for improving ovarian cancer diagnosis and treatment outcomes. Our prior study demonstrated that ARHGAP40 downregulation in basal cell carcinoma is attributed to CpG island hypermethylation. However, the expression and methylation status of ARHGAP40 in ovarian cancer remain unexplored. Here, we investigated ARHGAP40 protein expression in normal fallopian tubes, ovarian benign tumors, borderline tumors, low-grade serous carcinoma (LGSC) and high-grade serous carcinomas (HGSC). Methylation analysis of the ARHGAP40 was performed using bisulfite sequencing PCR (BSP). MethyLight assays were developed to detect methylated circulating tumor DNA (ctDNA) fragments of ARHGAP40. IHC results revealed absent or weak ARHGAP40 protein expression in 93.8% (30/32) of HGSC, 11.1% (2/18) of borderline tumors, and in 14.3% (1/7) of LGSC cases. ARHGAP40 protein expression was robust expressed in all normal fallopian tubes (15/15) and benign ovarian tumors (8/8). CpG island hypermethylation in the ARHGAP40 promoter showed a strong inverse correlation with protein expression (P < 0.001). Furthermore, methylated ctDNA for ARHGAP40 was detected in 80.0% (4/5) of HGSC patients’ plasma, but not in benign tumor (0/3) and healthy controls (0/15). Our findings suggest that promoter hypermethylation may be a mechanism underlying ARHGAP40 silencing in HGSC. Detection of methylated ARHGAP40 ctDNA may serve as a noninvasive biomarker for early diagnosis and monitoring of HGSC. While our findings suggest the potential of methylated ARHGAP40 as an early diagnostic biomarker, the small sample size warrants validation in larger cohorts.